Evaluasi Planned Delivery Time PT X - Filly Mustika Sunlo; I Gede Agus Widyadana (Jurnal Titra, 2020)
Purchasing department of PT X is in charge of procuring goods and one of the keys of good procurement process is Planned Delivery Time (PDT). PDT needs to be accurate so material arrives on time. The problem is PT X does not update and evaluate PDT regularly so the accuracy of current PDT is unknown. The purpose of this study is to minimize incompatibility between PDT with actual conditions. The suppliers to be analyzed are selected based on Pareto Principle. Analysis is done by comparing PDT with confidence intervals which are formed from the lead time in 2019. PDT that is out of CI needs to be corrected. The revision of PDT will be given based on mean value from actual lead time because mean generate the minimum error of PDT and lead time. CI can be used in the next evaluation of supplier performance. Another result of this study is a system that is designed to facilitate PT X in evaluating PDT. The system will process the purchase data and determine the material that need to be evaluated. The system also generate the mean value of lead time which can be used as a basis for determining PDT.